O ensino de leitura e escrita de alunos surdos em três escolas de comunidades do município de Moju – PA - MALCHER, Marcelle Cuimar (2023)
This study analyzed the difficulties that teachers from 03 public schools in communities of the municipality of Moju faced about the acquisition of reading and writing by deaf students. A quantitative and qualitative research was carried out to understand how inclusive work is taking place in these schools. The research was conducted through a questionnaire with 13 questions, of which only 07 will be used for analysis, applied withthe 05 teachers of Portuguese Language who work withdeafstudents,inmulti-roomclassrooms​. To compose the theoretical basis, we dialogue with the main authors Fernandes (2010), Quadros (2007), Aquino (2012) and others. The education of deaf people has been gaining ground in several researches in deafness and have pointed a long way to go, although they have made significant advances in the education of these people through laws that ensure an education directed specifically to them with specialized professionals. And recognition of their official language as their first language. From the field research, construction and analysis of the data,itwasconcludedthatthepublic-schoolsystemisundergoingaprocessof transformation regarding the inclusion of the deaf student, although slowly this process has been extended, fortunately it is Possible to identify the effort on the part of the teachers, to include these students.